Social and emotional learning - Humphrey, Neil (SAGE, 2013)
Social and emotional learning is a dominant orthodoxy in education systems around the world. This book provides the first in-depth, authoritative and balanced examination of the critical issues pervading the field. Each substantive aspect of SEL is examined through a critical lens, thanks to an extensive and thorough review of the international research literature.